Protective Efficacy Against Acute and Chronic Toxoplasma gondii Infection Induced by Immunization With the DNA Vaccine TgDOC2C - Zhang, Nian-Zhang; Gao, Qi; Wang, Meng; Hou, Jun-Ling; Zhang, Fu-Kai; Hu, Ling-Ying; Zhu, Xing-Quan (Frontiers in Microbiology, 2018)
Toxoplasma gondii is a ubiquitous intracellular apicomplexan parasite that can cause zoonotic toxoplasmosis. Effective vaccines against T. gondii infection are necessary to prevent and control the spread of toxoplasmosis. The present study analyzed the B-linear epitopes of T. gondii DOC2 (TgDOC2) protein and then cloned the C-terminus of the TgDOC2 gene (TgDOC2C) to construct the pVAX-TgDOC2C eukaryotic vector. After intramuscular injection of pVAX-TgDOC2C, immune responses were monitored. Two weeks after the last immunization, the protective effects of pVAX-TgDOC2C against acute and chronic toxoplasmosis were evaluated by challenges with T. gondii RH tachyzoites (genotype I) and PRU cysts (genotype II). The DNA vaccine elicited strong humoral and cellular immune responses with high levels of IgG antibody, IL-2 and IFN-γ production compared to those of the controls. The percentage of CD4+ and CD8+ T cells in mice immunized with pVAX-TgDOC2C was significantly increased compared to that of mice injected with empty pVAX I or PBS. After acute infection with 103 lethal tachyzoites, mice immunized with pVAX-TgDOC2C survived longer (12.5 days) than mice treated with pVAX I (8 days) and PBS (7.5 days). Mice immunized with pVAX-TgDOC2C had significantly less brain cysts (1600.83 ± 284.61) compared to mice immunized with pVAX I (3016.67 ± 153.84) or PBS (3100 ± 246.98). Together, these results demonstrated that TgDOC2C confers protective immunity against T. gondii infection and may be a promising candidate antigen for further development of an effective multicomponent vaccine for veterinary use against toxoplasmosis in livestock animals.